2011
DOI: 10.4161/hv.7.7.15997
|View full text |Cite
|
Sign up to set email alerts
|

Early clinical experience with a candidate meningococcal B recombinant vaccine (rMenB) in healthy adults

Abstract: Dull (2011) Early clinical experience with a candidate meningococcal B recombinant vaccine (rMenB) in healthy adults, Human Vaccines, 7:7, 781-791, DOI: 10.4161/hv.7.7.15997 To link to this article: https://doi.org/10.4161/hv.7.7.15997 IntroductionVaccination against invasive meningococcal disease is recognized as an optimal measure to prevent disability and mortality; however traditional approaches are not applicable to serogroup B because of the biochemistry of the capsular polysaccharide. 1-4Outer mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Since development, the 4CMenB vaccine has been administered in phase I, and pivotal phase IIb and III studies to over 8000 adults, adolescents and infants and has been shown to be immunogenic, as measured by serum bactericidal assay using human complement (hSBA), to a majority of tested strains within hypervirulent clusters responsible for MenB disease [16][17][18][19][20][21].…”
Section: Q5mentioning
confidence: 99%
“…Since development, the 4CMenB vaccine has been administered in phase I, and pivotal phase IIb and III studies to over 8000 adults, adolescents and infants and has been shown to be immunogenic, as measured by serum bactericidal assay using human complement (hSBA), to a majority of tested strains within hypervirulent clusters responsible for MenB disease [16][17][18][19][20][21].…”
Section: Q5mentioning
confidence: 99%
“…7 The resulting vaccine contains four protein antigens, 4CMenB (Bexsero ® , Novartis Vaccines, and Diagnostics), which has recently received approval for use from 2 mo of age by the European Medicines Agency (EMA). 8 This vaccine has been shown to be immunogenic and well tolerated when administered in various dose schedules in all age groups from infants to adults, 9,10 including toddlers and our own study in adolescents. We previously demonstrated the immunogenicity and tolerability of the serogroup B meningococcal vaccine, 4CMenB (Bexsero ® ), in 11-17 y-olds randomized to receive 1, 2, or 3 doses at 1, 2, or 6 mo intervals.…”
Section: Introductionmentioning
confidence: 99%
“…fHbp is a 28 kDa surface-exposed lipoprotein and an important component of two meningococcal vaccines currently in clinical development (6)(7)(8)(9). fHbp plays a prominent role in meningococcal pathogenesis by recruiting human factor H (hfH) to the bacterial surface, thus protecting the bacterium from complement-mediated killing (10)(11)(12).…”
mentioning
confidence: 99%